The analysis of the factors influencing the awareness of post-operative neurosurgery patients in the ICU of a hospital - Karo-Karo, Julyenni; Barita Aritonang; Desideria Yosepha Ginting (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Nurses' caring behavior significantly affects the quality of service and patient satisfaction. However, in Indonesia, the quality of nurses' caring behavior is still relatively low. High workloads and low work motivation can affect the quality of nurses' caring behavior. This study aims to analyze the relationship between work motivation and workload on nurses' caring behavior at Puskesmas Tigalingga in 2025.Objective: This study aims to determine the relationship between work motivation and workload on nurses' caring behavior at Puskesmas Tigalingga in 2025. Research Method: This study uses a quantitative design with a non-experimental descriptive correlation approach. The study was conducted at Puskesmas Tigalingga with a population of 57 nurses and midwives. The sampling technique used was Total Sampling. Data were collected using questionnaires and analyzed using Chi-Square tests and multiple logistic regression. Results: The results of the study indicate a significant relationship between work motivation and caring behavior (p-value = 0.003), as well as between workload and caring behavior (p-value = 0.003). Logistic regression analysis showed that workload has the greatest impact on caring behavior, with an Odds Ratio (OR) = 12.49. Conclusion: Managing workload effectively and increasing work motivation are crucial for improving nurses' caring behavior. Both factors play an important role in improving the quality of nursing services and patient satisfaction at Puskesmas Tigalingga.